QUANTIFYING WITHIN-MATCHES TACTICAL BEHAVIORS USING POSITION DATA AND NOTATIONAL ANALYSIS IN SOCCER: THE EFFECT OF GOAL SCORING (Kinesiology, 2024)
This study aimed to compare the collective and individual tactical positional behavior before the first goal was scored or conceded in official soccer matches. The sample comprised 50 players and 27 official matches played in Brazil during the 2020 and 2021 U-20 seasons. Global Positioning System devices were used to monitor the players’ positional data. Collective – width, length, length per width ratio, and stretching index, and individual – spatial exploration index, variables were calculated and compared between the contextual scenarios by a one-way ANOVA. Results indicated a reduction in the width after scoring a goal (p=.006) and a lower spatial exploration after conceding a goal (p